2021
DOI: 10.1002/anbr.202000027
|View full text |Cite
|
Sign up to set email alerts
|

Superenhanced Removal of Fungal Biofilms by Protease‐Functionalized Amphotericin B Nanocarriers

Abstract: A strong enhancement in the antifungal activity of amphotericin B (AmpB) encapsulated into shellac nanoparticles (NPs) surface functionalized with protease is reported. These AmpB‐loaded shellac NPs are fabricated by pH‐induced nucleation of aqueous solutions of shellac and AmpB in the presence of Poloxamer 407 (P407) as a steric stabilizer. The AmpB‐loaded shellac NPs are surface coated with the cationic protease Alcalase 2.4L FG. The performance of the AmpB‐encapsulated NPs against Candida albicans is evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 67 publications
0
25
0
Order By: Relevance
“…The same approach was found to work on fungal biofilms from Candida albicans, where the antifungal payload of AmphotericinB (AmpB) was loaded in shellac NPs. 155 Fig. 16F shows that after two-fold dilution of the stock AmpB-loaded shellac NP formulation and the free AmpB solution, there was a significant difference in the performance of these treatments.…”
Section: Polymeric Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation
“…The same approach was found to work on fungal biofilms from Candida albicans, where the antifungal payload of AmphotericinB (AmpB) was loaded in shellac NPs. 155 Fig. 16F shows that after two-fold dilution of the stock AmpB-loaded shellac NP formulation and the free AmpB solution, there was a significant difference in the performance of these treatments.…”
Section: Polymeric Nanoparticlesmentioning
confidence: 99%
“…16G. 155 5. The "benign-by-design" concept for antimicrobial nanocarriers Similar to the abuse of antibiotics, the commonly used formulations of antimicrobial nanoparticles use ubiquitous innocuous materials with relatively low biodegradability.…”
Section: Polymeric Nanoparticlesmentioning
confidence: 99%
“…The design of the NPs used in the current work is based on shellac core and P407. The fabrication of the current NPs was studied in the work done by Al-Obaidy et al 1,2 and Weldrick et al 3 The optimal precipitation conditions for such shellac NPs were found at pH 5.5, which was used for our following experiments. The primary purpose of the current work is to check the possibility of using the biofilm-infected 3D urothelial cell model for testing antimicrobial nanotherapeutics; the NPs were tested for their ability to act as nanocarriers for the antifungal agent.…”
Section: Fluconazole-loaded Shellac Nps' Encapsulation Efficiencymentioning
confidence: 99%
“…Some of these cationic nanoparticle formulations rely on electrostatic attraction with the negatively charged cell walls of microbial cells. Recently, active nanocarriers of both antibiotic and antifungal agents were developed with protease coating that can digest their way through biofilms delivering their payload to the embedded microbial cells [27][28][29]. However, in antimould applications, the strategy of using solely such electrostatic binding to the mould can be challenging due to the presence of other anionic species in the hyphae immediate environment which can render the treatment ineffective.…”
Section: Introductionmentioning
confidence: 99%